Nomenclatural and taxonomic updates on the Brazilian cuckoo-wasp catalogue (Hymenoptera, Chrysididae) - Rosa, Paolo; Brothers, Denis J. (Zootaxa, 2025)
Review of a recent catalogue of the Chrysididae of Brazil has provided an opportunity for several taxonomic and nomenclatural updates and corrections within the family. Discussions of 67 taxa and photographs of type specimens of 30 taxa support the following proposals: inclusion of the overlooked taxa Boffachrysis Pagliano & Scaramozzino, 1990, replacement name for Brethesiella Linsenmaier, 1987, and Neochrysis (Ipsiura) aemula ssp. agnata Linsenmaier, 1997; resurrection from synonymy of Caenochrysis aptata (Linsenmaier, 1984) stat. resurr., Cae. invisa (Linsenmaier, 1984) stat. resurr., Cae. scyphiphora (Linsenmaier, 1984) stat. resurr., Cae. turmalina (Linsenmaier, 1984) stat. resurr., Chrysis aequinoctialis Dahlbom, 1854 stat. resurr., Chr. anceps Gribodo, 1879 stat. resurr., Chr. binominata Mocsáry, 1889 stat. resurr., Chr. chiriquensis Bischoff, 1910 stat. resurr., Chr. cognata Gribodo, 1879 stat. resurr., Exsecochrysis gracilia (Linsenmaier, 1985) stat. resurr., Ipsiura aemula (Linsenmaier, 1985) stat. resurr., I. amaurotica (Linsenmaier, 1985) stat. resurr., I. anisitsii (Brèthes, 1906) stat. resurr., I. superleucocheila (Linsenmaier, 1985) stat. resurr., Neochrysis glabriceps (Ducke, 1903) stat. resurr., and N. transstriata Linsenmaier, 1985 stat. resurr.; synonymizations of Chr. aperta du Buysson, 1898 syn. nov. and Chr. hexodontophora Bischoff, 1910 syn. nov. = Chr. anceps Gribodo, 1879, Chr. roseni Mocsáry, 1912 syn. nov. = Chr. fuscipennis Brullé, 1846, Chr. peruviana du Buysson, 1898 syn. nov. and Chr. schulthessi Mocsáry, 1889 syn. nov. = Chr. aequinoctialis Dahlbom, 1854, and Neochrysis (Ipsiura) sobrina Linsenmaier, 1985 syn. nov. = Ipsiura fritzi Bohart, 1985; restriction of Exsecochrysis Linsenmaier, 1985 to include only Exsecochrysis adnexa (Linsenmaier, 1997), E. alfkeni (Ducke, 1902), E. allotria (Linsenmaier, 1985) and E. gracilia (Linsenmaier, 1985); and reinstatement of two genera as valid: Boffachrysis Pagliano & Scaramozzino, 1990, including Boffachrysis acuta (Brèthes, 1906) comb. nov., B. ancilla (du Buysson, 1898) comb. nov., B. cavifrons (Brullé, 1846) comb. nov., B. charruana (Brèthes, 1902) comb. nov., B. dolosa (du Buysson, 1898) comb. nov., B. fasciifera (Bischoff, 1910) comb. nov., B. imbecilla (Mocsáry, 1889) comb. nov., B. jenseni (du Buysson, 1906) comb. nov., B. lagopus (du Buysson, 1891) comb. nov., B. leucophris (Mocsáry, 1889) comb. nov., B. morosa (du Buysson, 1901) comb. nov., B. postica (Brullé, 1846) comb. nov., B. simulator (Kimsey, 1985) comb. nov. and B. ypirangensis (du Buysson, 1904) comb. nov.; and Rhipidochrysis Rosa & Pavesi, 2023 including only Rh. bruchi (Brèthes, 1903). The lectotype of Holopyga kohli du Buysson, 1901 is designated. The correct spellings are determined for Duckeia gracilis Kimsey, 1987, Chrysis leucophris Mocsáry, 1889, Holophris albolimbata (Ducke, 1908), Holopyga luzulina Dahlbom, 1854, Holopyga wagneriella du Buysson, 1904 and Cleptes buyssoni Ducke, 1905. Corrections to type statuses and type depositories are given, and the applications of several articles of the International Code of Zoological Nomenclature are discussed.